Opera directing in Slovenia between the two wars - Koter, Darja (Muzikološki zbornik, 2012)
The article deals with opera directing in Slovenia between the two wars, with the emphasis on opera performances of the National Theatre in Ljubljana. The author introduces a profile of an opera director in relation to theatre directing as well as some important European theatres and schools, and assesses the interactions between theatre and opera performances that were directed by some of the most notable stage directors of the Ljubljana Drama Theatre, such as Osip Šest, Bratko Kreft, and Ciril Debevec.
Keywords: Debevec, Ciril, 1903-1973; Drama; Kreft, Bratko, 1905-1996; Ljubljana; Ljubljana Drama Theatre; Narodno gledališče; National Theatre; opera directing; operna režija; Šest, Osip, 1893-1962